Technology Park Malaysia the Quality of Research & Development in Biotechnology - Nik Mustafa, Nik Hazma (1997)
Research and development is an area that guarantees the development of products and services of companies. With research, company will be able to explore the possible potential opportunities to be better off in future days and with development, companies that equipped with research activities will go through the possible growth. The word 'research', which comes from two (2) words; re and search can be defined as continuous and explore. The searches for new things are never ends. The explore must be in continuous form. Explore means find and gather for solutions. While continuous means progressively involved in sustaining or maintaining such exploration. Research and development is a base for growth. It is a root where an extensive, unique and useful philosophy of doing things lie. ''Research usually is considered to be studious inquiry or examination, especially investigation or experimentation aimed at the discovery and interpretation of facts and the revision of accepted theories or laws in the light of new facts." (George, 1992, p27) Research is categorized into two (2) categories; basic research and applied research. Basic research is a research conducted to understand the nature of the